2000
DOI: 10.1109/18.857795
|View full text |Cite
|
Sign up to set email alerts
|

Model-based classification of radar images

Abstract: Abstract-A Bayesian approach is presented for model-based classification of images with application to synthetic-aperture radar. Posterior probabilities are computed for candidate hypotheses using physical features estimated from sensor data along with features predicted from these hypotheses. The likelihood scoring allows propagation of uncertainty arising in both the sensor data and object models. The Bayesian classification, including the determination of a correspondence between unordered random features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(28 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…ASCs are local descriptors with rich, physically relevant information. It is demonstrated that ASCs can be handle various EOCs with good performances [20][21][22][23][24]. For the test samples, which cannot be reliably classified by CNN, they are possibly from EOCs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…ASCs are local descriptors with rich, physically relevant information. It is demonstrated that ASCs can be handle various EOCs with good performances [20][21][22][23][24]. For the test samples, which cannot be reliably classified by CNN, they are possibly from EOCs.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering center features reflect the electromagnetic scattering characteristics of the target such as attributed scattering centers (ASCs) [18,19]. ASCs describe the local structures of the target by several physically relevant parameters, which have been demonstrated notably effectively for SAR ATR especially under the extended operating conditions (EOCs) [19][20][21][22][23][24][25]. In [21], an ASC-matching method is proposed based on Bayesian theory with application to target recognition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, such methods suffer from severe overfitting [5]. Model-based methods were proposed to solve the above problem [6,7]. In the model-based methods, SAR images are predicted by computer-aided design model and the modeling procedure is usually complicated.…”
Section: Introductionmentioning
confidence: 99%